1998
DOI: 10.1161/01.str.29.4.759
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Atherosclerosis in Relation to Hysterectomy Status in Black Women

Abstract: Background and Purpose-This study was designed to investigate whether black women who underwent hysterectomy only (nϭ59) or hysterectomy plus bilateral oophorectomy (nϭ25) were at increased risk of subclinical carotid atherosclerosis compared with black women who underwent natural menopause (nϭ54). The effects of both surgery and menopausal status were evaluated. Methods-Women aged 34 to 58 years were recruited from the Pittsburgh, Pa, area. Postmenopausal status was defined as a serum follicle-stimulating hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Two studies have shown that women who had undergone hysterectomy with ovarian conservation were equally or less likely to be using hormone therapy than women with bilateral oophorectomy or women without hysterectomy. 28,29 We did not have complete information concerning the use of hormonal therapy after the index date. This information was not available electronically in the REP until 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown that women who had undergone hysterectomy with ovarian conservation were equally or less likely to be using hormone therapy than women with bilateral oophorectomy or women without hysterectomy. 28,29 We did not have complete information concerning the use of hormonal therapy after the index date. This information was not available electronically in the REP until 1998.…”
Section: Discussionmentioning
confidence: 99%
“…African-American women have been reported to have 2–3 times the risk of UF than White women [6], [13], a difference that could not be explained by ethnic differences in hormone levels and other known risks [3], [6]. In comparison with White women, Black women have a higher prevalence of hypertension, diabetes and obesity [14], which are independently associated with UF [12], [15], [16]. These factors are also common cardiovascular risks and might be related to atherosclerosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in prothrombotic factors and markers of platelet dysfunction also returned to prehysterectomy levels. In premenopausal black women, focal carotid plaque was found to be present in 20% of subjects compared with 48% of hysterectomy patients [11]. Among postmenopausal women, plaque was present in 73% of nonusers, but present only in 33% of women on HRT.…”
Section: Menopause and Cardiovascular Diseasementioning
confidence: 92%